2014
DOI: 10.1090/s1088-4173-2014-00269-0
|View full text |Cite
|
Sign up to set email alerts
|

Classification of subdivision rules for geometric groups of low dimension

Abstract: Abstract. Subdivision rules create sequences of nested cell structures on CWcomplexes, and they frequently arise from groups. In this paper, we develop several tools for classifying subdivision rules. We give a criterion for a subdivision rule to represent a Gromov hyperbolic space, and show that a subdivision rule for a hyperbolic group determines the Gromov boundary. We give a criterion for a subdivision rule to represent a Euclidean space of dimension less than 4. We also show that Nil and Sol geometries ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Because Γ n might not be connected, δ n might take the value ∞. Following Rushton [23], we define a transition function f m,n : Γ n → Γ m for all integers m, n ≥ −1 such that m ≤ n. Let t be a tile of R n (S 2 ). Then f (v(t)) = v(s), where s is the tile of R m (S 2 ) which contains t. We extend f m,n to the edges of Γ n in the straightforward way, so that f m,n is a cellular map.…”
Section: The Fat Path Subdivision Graphmentioning
confidence: 99%
See 1 more Smart Citation
“…Because Γ n might not be connected, δ n might take the value ∞. Following Rushton [23], we define a transition function f m,n : Γ n → Γ m for all integers m, n ≥ −1 such that m ≤ n. Let t be a tile of R n (S 2 ). Then f (v(t)) = v(s), where s is the tile of R m (S 2 ) which contains t. We extend f m,n to the edges of Γ n in the straightforward way, so that f m,n is a cellular map.…”
Section: The Fat Path Subdivision Graphmentioning
confidence: 99%
“…For the proof, we use some general results of Rushton [23]. These lead to a condition on R which is necessary and sufficient for the fat path subdivision graph to be Gromov hyperbolic.…”
Section: Introductionmentioning
confidence: 99%
“…(Note: In [11], we used an alternative definition for history graph that had a vertex for every cell of any dimension in Λ n , with edges being induced by inclusion. However, the two history graphs are quasi-isometric when any top-dimensional cells that intersect do so in a codimension 1 subset.…”
Section: Definitionsmentioning
confidence: 99%
“…Proof. In [11], we showed that the limit set Λ of a subdivision pair whose history graph is quasi-isometric to a hyperbolic group G has a canonical quotient onto the Gromov boundary ∂G, with connected preimages.…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation